The angiotensin II type 2 receptor activates flow-mediated outward remodelling through T cells-dependent interleukin-17 production. Issue 1 (21st June 2016) - Caillon, Antoine; Grenier, Céline; Grimaud, Linda; Vessieres, Emilie; Guihot, Anne-Laure; Blanchard, Simon; Lelievre, Eric; Chabbert, Marie; Foucher, Etienne D.; Jeannin, Pascale; Beauvillain, Céline; Abraham, Pierre; et al.
Abstract: Aims: The angiotensin II type 1 receptor (AT1R) through the activation of immune cells plays a key role in arterial inward remodelling and reduced blood flow in cardiovascular disorders. On the other side, flow (shear stress)-mediated outward remodelling (FMR), involved in collateral arteries growth in ischaemic diseases, allows revascularization. We hypothesized that the type 2 receptor (AT2R), described as opposing the effects of AT1R, could be involved in FMR. Methods and results: We studied FMR using a model of ligation of feed arteries supplying collateral pathways in the mouse mesenteric arterial bed in vivo . Seven days after ligation, diameter increased by 30% in high flow (HF) arteries compared with normal flow vessels. FMR was absent in mice lacking AT2R. At Day 2, T lymphocytes expressing AT2R were present preferentially around HF arteries. FMR did not occur in athymic (nude) mice lacking T cells and in mice treated with anti-CD3ε antibodies. AT2R activation induced interleukin-17 production by memory T cells. Treatment of nude mice or AT2R-deficient mice with interleukin-17 restored diameter enlargement in HF arteries. Interleukin-17 increased NO-dependent relaxation and matrix metalloproteinases activity, both important in FMR. Remodelling of feeding arteries in the skin flap model of ischaemia was also absent in AT2R-deficient mice and in anti-interleukin-17-treated mice. Finally, remodelling, absent in 12-month-old mice, was restored by a treatment with the AT2R non-peptidic agonist C21. Conclusion: AT2R-dependent interleukin-17 production by T lymphocyte is necessary for collateral artery growth and could represent a new therapeutic target in ischaemic disorders.